An Instrumented Insole for Long Term Monitoring Movement, Comfort, and Ergonomics - Cristiani, Andrea M.; Bertolotti, Gian Mario; Marenzi, Elisa; Ramat, Stefano (IEEE sensors journal, 2014)
We present a new electronic insole for wireless monitoring of motor activities and shoe comfort. The proposed device, equipped with both ZigBee transmission and local data storage allows unobtrusive, long term monitoring of subjects outside the laboratory, during natural behavior activites, such as daily living and sports. The system detailed in this work includes humidity and temperature sensors, as well as a three axis accelerometer and four pressure sensors, all fitted within a 3.7 mm thick insole. Preliminary experiments have shown that the device is reliable and may be worn without causing discomfort even for long periods of time, suggesting that it could be useful in applications ranging from ergonomics studies on footwear to sports and rehabilitation.